VIRTUALITY IN TUTORING: AN APPROACH TO ANALYSIS OF SPANISH UNIVERSITIES - Toledo Lara, Gustavo Eduardo (2017)
The European university reform process requires a new approach into the relationship between faculty and students. This paper analyzes how the Spanish university context has demanded adaptations for the faculty’s role in the presence of new technologies, identifying the relevance of virtual tutoring as an opportunity to understand another meaning of the teaching and learning process. From a qualitative standpoint, the topic of study is addressed in order to characterize the Spanish university context and virtual tutoring. The faculty’s training need is identified beyond promoting academic research, in addition to proposing a new classification of virtual tutoring based on five levels. Finally, Bologna centers its attention on the student; however, the practices established before the reform are still ongoing. Virtual tutoring, together with the motivational factor, constitutes one of the most decisive actions.